(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
This study was carried out to investigate a possibility of the fungus (Penicillium chrysogenum Thom) to produce lovastatin compound by using solid substrate fermentation method (ssf) in the presence of a mixture of three organic substrates (wheat bran, oat bran, soybeans), carbon and nitrogen sources (potato peels powder, yeast extract, milk powder). The effectiveness of the obtained lovastatin compound was tested with concentrations of (0.5, 1, 2, 4) mg/ml in inhibiting the growth of pathogenic fungus (Aspergillus fumigatus Fresenius). The analysis of sample of obtained extract by using an infrared spectroscopy device (FTIR) showed presence of several of functional groups belong to lovastatin compound such as (hydroxil, methyl, lactone, and ester). The average of concentration of lovastatin compound in fermentation experments reached (21.5, 27.1, 41.83, 25.03) mg/g dry substrate in the days (4, 7, 10, 13) respectlively. The obtained lovastatin compound showed inhibiting the growth of the fungus (A.fumigatus) with inhibitory ratios reached (72.12, 73.93, 78.78, 89.09)% at concentrations (0.5, 1, 2, 4) mg/ml respectively.